2019
DOI: 10.1007/s13201-018-0890-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical processes in the groundwater environment of Batlagundu block, Dindigul district, Tamil Nadu: conventional graphical and multivariate statistical approach

Abstract: Water quality assessment is essential to ensure viable safe use of the resources for drinking, agricultural and industrial purposes. Deterioration of groundwater quality due to anthropogenic activities is increasing at an alarming rate in most parts of Dindigul district, but limited work has been carried out on groundwater quality and monitoring. This paper highlights the groundwater quality and compares its suitability for drinking and irrigation purpose of Batlagundu block in Dindigul district of Tamil Nadu.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Chlorides correlated positively with T (0.510), pH (0.846), EC (0.809), TDS (0.600), Salinity (0.733), TA (0.696), and Hardness (0.908). The hardness-chloride relationship matches with the findings of Umamageswari et al (2019).…”
Section: 11supporting
confidence: 85%
“…Chlorides correlated positively with T (0.510), pH (0.846), EC (0.809), TDS (0.600), Salinity (0.733), TA (0.696), and Hardness (0.908). The hardness-chloride relationship matches with the findings of Umamageswari et al (2019).…”
Section: 11supporting
confidence: 85%
“…Total hardness was the most critical factor in critical box plots, with calcium and magnesium being the primary ions at sample sites 5 and 6. During several sample sites in 2015, Umamageswari et al, ( 2019 ) showed a similar trend of box plots for groundwater assessment. Groundwater is contaminated with dangerous metals and ions due to weathering of rocks and minerals, industrial effluents and wastes, and sewage runoff (Sharma & Bhattacharya, 2017 ; Vetrimurugan et al, 2017 ).…”
Section: Resultsmentioning
confidence: 56%
“…This leads to the evolution of the Ca-SO 4 , Mg-SO 4, and Na 2 SO 4 water types, reaching an advanced state of geochemical evolution represented by the Na-Cl type. Figure 8 shows that the groundwater of the seven aquifers is mainly plotted in Mg-SO 4 Limited reverse ion exchange has been noticed at two locations within Mullusi aquifer and Mullusi-Ubaid aquifers. Mixing with the underlying dense saltwater is another source of salinization of groundwater from the aquifer, mostly caused by intense pumping (10).…”
Section: Hydrochemical Facies and Geochemical Evolution Of Groundwatermentioning
confidence: 99%
“…Spatial analysis techniques can help to estimate, and manage the groundwater assessment; for example in India and Nigeria, the assessment is essential for strategies to protect groundwater and land use (1). The recent international practices in groundwater characterization have been reviewed by several studies (2)(3)(4). Mohamed and Allia (5) have studied the geochemistry of the aquifer based on the ionic components, hydrochemical facies, and the factors controlling groundwater chemistry in the Souf valley of Sepentrional Saha (Algeria), using different graphical plots.…”
Section: Introductionmentioning
confidence: 99%